Business System Information Analysis Process Outcome in Hospital General Bengkayang Area - Angelia Chantika Sri Margiawati; Gusti Syarifudin; I Dewa Ayu Eka Yuliani; Sandy Kosasi; Budi Susilo (CCIT Journal, 2023)
In the application of the outpatient information system business process at the Bengkayang Regional General Hospital, there are still problems faced, namely the occurrence of incompatibility of patient medical data information in the examination section / poly section, resulting in delays in the patient handling process. This is the background for the author to analyze the business process of outpatient system information at the Bengkayang General Hospital using the Business Process Management Life Cycle method. This study aims to determine how effective it is in managing the outpatient information system business process at the Bengkayang Regional General Hospital. The analytical technique used is BPMN, value chain, business area analysis and the method used is the BPM life cycle. The results of this study can support the current business processes for the better. With the addition and improvement of optimal technology, with existing information system technology to obtain a more detailed and complete procedural flow chart. The resulting procedure flow chart will integrate the data in each part of the service unit in the outpatient department, so that the data can be used together between departments so that data duplication can be avoided.